Impact of Internet Medical Information on Patient-Doctor Relationship in Al-Hilla City - Hameed, Huda Ghazi; Farhod, Mehasin Abdali (Medical Science Journal for Advance Research, 2025)
Background: Patient engagement with online health has increased before seeking professional guidance. The surge in patient use of online health information is poised to reshape healthcare consultations. This influences how patients interact with their physicians, participate in discussions, and ultimately perceive the doctor-patient relationship. Aim: To determine the extent to which patients use the Internet for medical information and its impact on patient-doctor relationships. Patient and Method: A cross-sectional study was conducted on 432 patients who attended the outpatient clinic of Merjan Teaching Hospital and Al-Sadiq General Teaching Hospital in Al-Hilla City, Iraq, data collected from the 1st of May , 2024 to the 31st of August ,2024. A well-structured questionnaire was used containing questions about the participants’ sociodemographic features and questions to assess patients’ online health information-seeking behaviors and their awareness of the Internet’s impact on the patient-doctor relationship. Data were analyzed using the SPSS program version 27. Results: The mean age of study participants was (34.25 ± 10.47 years). The largest age category was 26-45 years (67.4%), and (57.2%) were females. The Internet for medical information was used by 91% of the patients. Regarding health behavior, the therapeutic topic was the common topic searched by half of the study participants (50.3%). More than half of the participants believed that seeking online health information improves the patient-doctor relationship (59%). Concerning internet use, a greater rate of internet utilization was significantly recorded among the age group (26-45 years) (P=0.001), housewives (P=0.046) and high levels of education (P=0.02). Also, Internet users spend significantly more time online than nonusers (p=0.002). Conclusions: A high proportion of patients use the Internet to get medical information, significantly more among younger age groups, housewives, and a high level of education: health education and initiatives to encourage eHealth as an effective health intervention and care platform.